The economic partnership between India and Taiwan in a Post-ECFA ecosystem - Karackattu, Joe Thomas (SpringerBriefs in Economics, 2013)
The partnership between India and Taiwan is situated in a virtual maze of complex political factors. Given the core issue of contestation of Taiwan's political status in world affairs and India's adherence to the "One China" policy, the relationship remains a fragile one for both partners. In recent years, Taiwan has signed the Cross-Strait Economic Cooperation Framework Agreement (ECFA) with Mainland China. Increasingly, its political and economic future (including its relationships with countries such as India) will continue to be linked with Mainland China.   This book closely examines the partnership between India and Taiwan within the new post-ECFA setting that Taiwan finds itself in. It explicates the shifts and continuities in Taiwan's economic relationship with Mainland China, discusses how partnership with India could become a crucial pivot of Taiwan's foreign policy in the coming years, and argues why this partnership is vital for the "take-off " of India's own economic growth targets. The book identifies specific avenues for India and Taiwan to benefit from the economic growth success stories that they have come to represent over these years and outlines policy realignments that could allow India and Taiwan to best realize their mutuality of interests.